Trading Mechanisms and Price Volatility: Spot Versus Futures - Park, Hun Y. (The Review of Economics and Statistics, 1993)
This paper compares the volatility of spot prices with that of futures prices using two estimators of volatility–natural and temporal. Using intraday data of the Major Market Index and its futures prices, the author shows that the well-known U-shaped volatility patterns during the day are not necessarily due to trading mechanisms. The author also shows that, when a temporal estimator is substituted for a natural estimator, th e U-shaped patterns disappear in both the spot and futures markets. Th e author provides some reasons why a temporal estimator may add more information. Copyright 1993 by MIT Press.